Insights for the Drop-off/Pick-up Method to Improve Data Collection. Issue 1 (2nd January 2023) - Junod, Anne N.; Jacquet, Jeffrey B.
Abstract: Mail and telephone surveys are becoming increasingly expensive and unreliable, while internet-based surveys raise issues of geographic representation and other matters of authenticity. The Drop-Off/Pick-Up (DOPU) method is an alternative which can elicit higher response rates and reduce non-response bias issues. DOPU involves dropping off and picking up surveys in person and can yield high participation because personal interactions have been shown to stimulate norms of reciprocity. We share insights from our 2019 DOPU study of hydrocarbon energy export impacts in four communities that have experienced oil-by-rail transportation and related disasters, with surveys collected in two metropolitan and two rural communities in the U.S. Midwest and Pacific Northwest. We organize and present a suite of novel and established recommendations suitable for both scholarly and community-based researchers and practitioners to strengthen community support, improve fieldwork efficiency, increase response rates, and reduce costs in future DOPU studies.